Adaptability in socio-political contexts: Moving beyond ability and intelligence - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
The ability to adapt in an ever-changing environment is critical for success, if not, survival. Most people would acknowledge that change management can sometimes be a discomforting and bumpy process. This applies not just with individuals and organisations, but also with governments. While the former two may adapt privately, governments, represented by politicians and public officers, often have the unenviable task of demonstrating adaptability under the watchful eyes of their public. Slip-ups, trips and falls thus come at greater costs, which go well beyond mere embarrassment.